Structure and Dynamics of Phytoplankton Populations in the Black Sea from 2014 to 2017 - SAHIN, FATIH (Mediterranean Marine Science, 2024)
This study investigated the seasonal variations in phytoplankton communities along the Turkish Black Sea coast (2014-2017). Analyzing data from 20 stations revealed high biodiversity (175 species across 14 classes). Phytoplankton abundance showed distinct seasonality, with a peak in summer (2017, 96.6%) and lows in winter, characterized by dinoflagellate dominance. In terms of biomass, diatoms dominated in half of the sampling seasons, while dinoflagellates dominated in the other half at the surface during the study period. The dominance of dinoflagellates corresponded to the winters and summers of 2015 and 2016. The winter conditions of 2015 were harsh. The surface water community composition sometimes varied from that of the water column. Importantly, 44 potentially toxic species were identified, comprising 25% of the community and significantly contributing to both abundance (73.2-98.6%) and biomass (64-90.2%) throughout the year. These results highlight the unique structure of the Black Sea phytoplankton community, characterized by seasonal dominance of diatoms and a significant presence of potentially toxic species. Season, year, and water depth significantly influenced the phytoplankton assemblages. Water temperature was negatively correlated with dissolved oxygen and nitrogen-based nutrients.